Characteristics of propeller jet flow within developing scour holes around an open quay - Wei, Maoxing (2020)
By using the particle image velocimetry (PIV) technique, experimental results of the propeller jet flow field within a developing scour hole around an open quay are presented. The experiments were conducted with four toe clearances (defined as the longitudinal distance between the propeller face and toe of the quay slope), which account for three distinct scour profiles corresponding to the three toe clearance fields, namely, near, intermediate, and far clearance fields. To better understand the underlying scour mechanisms associated with each field, the mean flow fields at selected time intervals (t = 0, 0.5, 2, 12, and 48 h) are presented in vector and streamline plots. The data provide an improved understanding of the development of the main jet flow and vortex that formed in front of the quay slope. The importance of both the main jet flow and vortex in terms of their contribution in shaping the final scour profile in each field is discussed. Moreover, the turbulence intensities and near-bed Reynolds stress, which are analyzed for the intermediate field, exhibited a declining trend with the development of the scour hole.